Analisis Pengaruh Sisa Klor Terhadap Air Distribusi PDAM Surya Sembada IPAM Karang Pilang 3 Kota Surabaya - M. Miftahul Huda; Rafif Permata Dwidewitra; Tuhu Agung Rachmanto (Pusat Riset dan Inovasi Nasional, 2024)
The provision of drinking water for the community must meet quality standards that include physical, chemical and bacteriological aspects. The use of chlorine gas as a disinfectant can affect the quality of drinking water in an installation. One method to reduce bacteria in the water treatment process is to use disinfectants, among which chlorine is often used. The use of chlorine as a disinfectant in water treatment plays an important role in eliminating bacteria in water. This research aims to evaluate the quality of water treated by PDAM Surya Sembada, with the hope of providing an understanding to the public about the impact of residual chlorine on distributed water